Роль співця у києворуській та скальдичній поезії доби Середньовіччя (на прикладі «Слова о полку Ігоревім») - Блик О. (Літературознавчі обрії. Праці молодих учених, 2010)
Basing on Dmitriy Likhachov’s research we hypothesize the existence of professional secular poetry in ancient Russian literature. Comparing the role of scalds in Scandinavian society and the functions of «The Tale of Igor’s Campaign» author we defined some typological similarities. Considering the significant economical and political ties between Kievan Rus and Scandinavia and the fact that scalds often visited Kyiv court as the members of Scandinavian forces we can predict definite influences of skaldic poetry on «The Tale of Igor’s Campaign» stylistics.